Isolation, Identification, and Evaluation of Antimicrobial of the LAB from Bekasam: The Traditional Fermented Fish in Indonesia - Nur Rohman; Muhammad Bachrun Alim (Biology, Medicine, & Natural Product Chemistry, 2025)
Lactic acid bacteria (LAB) are frequently utilized in fermented foods and can incresed shelf life for the products through their secondary metabolites includes carbon dioxide, hydrogen peroxide, lactic acid and bacteriocins. Beside increasing the shelf life, LAB also affect taste, smelt, and texture. Thus, this study aimed to isolate, identify and evaluate antibacterial LAB strains from Indonesian traditional fermented fish (Bekasam). Gram staining, the catalase assay, and motility assays were used to initially characterize the presumed isolates phenotypically following primary isolation on De Man, Rogosa, and Sharper (MRS) agar. 14 isloates were determined to be presumed LAB by preliminary phenotypic testing. One species that has the highest antibacterial activity is confirmed by a 16S rRNA sequencing study. Lactobacillus plantarum CP-134 was identified from the bekasam. In the biochemical characterization all isolates were catalase-negative and non-motile. According to our research, these LAB strains may have applications in fermented foods due to their probiotic properties, which include antibacterial activity. They might be used as natural substitutes for additives and antibiotics, but more in vivo or in silico research is required to verify their potential and effectiveness. A typical traditional food preservation technique for enhancing shelf life, food safety and nutrition and sensory qualities is fermentation. Bekasam is a traditional fermented food from Indonesia.